Modelagem baseada em grafo para detecção de regiões de anomalias em termografia de mama - PONTES, Stefano Walker Pereira (2019)
The most common type of cancer, among women, occurs in the breasts. As the prevention is still difficult, due to several factors, early diagnosis is primordial in order to increase the survival rate of those affected. Therefore, much effort is dedicated to improving diagnostic methods by increasing of accuracy, and reduction of the imaging tests cost. In this context, thermography appears as a promising examination, with a series of advantages, but still in evolution. This work aims to provide a methodology for detection of abnormalities regions in breast thermography. In this methodology are combined superpixel segmentation, graph construction and analysis of complex network measurements. In the construction of the graph, each superpixel becomes a node of the graph and the adjacency relations between the regions becomes the edges, whose weights are determined by functions. The generated graphs are applied threshold variations to highlight the characteristics of small world networks. After several experiments involving graph measurements and community analysis, the detected regions are evaluated according to the proposed evaluation method. The evaluation of the detection performed in the methodology experiments provided results that can still be improved, in relation to the detection of the exact region of the anomalies, with a percentage of 59.1 %. However, it produced significant results, in order to indicate in which breast there is an anomaly, with a success rate of 86.4%.